Experimental modeling of the relationship between adhesion and friction forces in assessing the stickiness of materials - Grigorev P.A.; Sladkova L.A. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta, 2023)
Sticking of various materials on contacting surfaces is a problematic task in various areas of the national economy, as it leads to an increase in digging efforts, a decrease in productivity and, as a result, an increase in economic costs. For ground-based transport and technological complexes, soil sticking is characteristic of the surfaces of the working bodies of earthmoving and agricultural machines, conveyor belts, walls of mixing plants, etc. The process of sticking has not been fully studied, both from the standpoint of experimental and theoretical studies. Experimental modeling of the detection and evaluation of stickiness will reveal not only its physical nature, but also find certain relationships and dependencies in the evaluation of the friction forces of the soil, which indicates their change in the direction of increase with a decrease in the speed of movement of the contacting body. The reason for this is the presence of sticky forces between the contacting surfaces. The results obtained were achieved on the basis of mathematical apparatus and energy efficiency, as well as modeling the process of changing friction forces de-pending on the adhesive properties of the surface.